Variability in Wild and Farmed Golden Rabbitfish Siganus guttatus Bloch (Perciformes: Siganidae in Northern Mindanao) - Gorospe, Jessie; Demayo, Cesar (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Variations in wild andfam1ed golden rabbit.fish were investigated based on qualitative and quantitative descriptions of internal body parts ·and morphomeristic characters. Thirty OTU’s (operational taxonomic units) equally representing the different populations were collected and measured although only twenty (20) characters were indentified into quantitative morpological, meristic and qualitative morphological characters. Results of cluster analysis of the various characters show high variability was observed in wild than in farmed populations of the fish.